KONSEPSI NEGARA KESEJAHTERAAN PADA KONTEKS PEMBANGUNAN WILAYAH - Irwan Suhermi (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2017)
Abstract: The implementation of regional development in Indonesia can not be separated  from  the  process  of  adoption  from  the  development  theory  that developed by west experts in the regional planning. In the era of regional autonomy, regional development plays a very important in the development of Indonesia. By using secondary data, this paper tries to explore the development of the region conducted in Indonesia is associated with the concept of a welfare state. The paper ends with a proposed regional development strategy in the future. Kata kunci: Negara kesejahteraan, pembangunan wilayah